Some reflections on the early discussion concerning the ṣifāt Allāh: cross-fertilization and cooperation in the Islamic milieu' - Keating, Sandra Toenies (Islam and Christian-Muslim relations, 2011)
Although it has fallen out of favour in contemporary theology, the activity of interreligious apologetics has historically allowed very difficult and controversial questions to be raised and examined within the parameters of a controlled intellectual environment. As an illustration of this phenomenon, this paper examines the thought of three scholars, Jahm ibn Ṣafwan, Aḥmad ibn ?anbal, and Abū Rā'iṭa al-Takrītī, who were involved the debates of the eighth and ninth centuries concerning the divine attributes. They facilitated the encounter among different systems of thought, such as neo-Platonism, Christianity and Islam, creating the opportunity for both cross-fertilization and more precise articulation of individual doctrines. These Muslim and Christian intellectuals, while holding very different views of God and revelation, simultaneously saw themselves as engaged in a common project of formulating the foundation for society based on the will of God that had long-lasting effects.